PENGARUH RASA INGIN TAHU TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Asoka Niscahya Alam Mayang; Nita Karmila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low mathematics learning outcomes of fifth grade students which are influenced by a lack of curiosity are the background for this research. This research aims to determine the effect of curiosity on the mathematics learning outcomes of fifth grade elementary school students on the volume of cubes and blocks. This research is quantitative research with a causal approach which aims to determine the effect of curiosity on mathematics learning outcomes. This research was conducted on class V students at Kotabatu 8 State Elementary School, Bogor, with a population of 81 students and a sample of 45 respondents. This research data was obtained through distributing instruments in the form of questionnaires for the curiosity variable and instruments in the form of questions for the mathematics learning outcome variable. The research results show that there is an influence of curiosity on mathematics learning outcomes with a regression coefficient (rxy) of 0.45 and a tcountof 3.32, while the coefficient of determination (r2) is 0.2025 or 20.25%. This means that 20.25% of students' mathematics learning outcomes are determined by curiosity through the regression equation Ý = (6.20 +0.55x) while the remaining 79.75% is determined by other factors. Based on the research results above, it can be concluded that there is a positive and significant influence of curiosity on mathematics learning outcomes.